Patterns of intimate partner violence among perinatal women with depression symptoms in Khayelitsha, South Africa: a longitudinal analysis. (12th April 2018) - Schneider, M.; Baron, E.; Davies, T.; Munodawafa, M.; Lund, C.
Abstract : Background: A combination of intimate partner violence (IPV) and depression is a common feature of the perinatal period globally. Understanding this association can provide indications of how IPV can be addressed or prevented during pregnancy. This paper aims to determine the prevalence and correlates of IPV among pregnant low-income women with depressive symptoms in Khayelitsha, South Africa, and changes in IPV reports during the course of the perinatal period. Methods: This study is a secondary analysis of data collected as part of a randomised controlled trial testing a psychosocial intervention for antenatal depression. IPV, socio-demographic measures, depression and other mental health measures were collected at recruitment (first antenatal visit), 8 months gestation, and 3 and 12 months postpartum. IPV was defined as a sexual or physical violence perpetrated by the participant's partner in the past 3 months. Descriptive statistics are reported. Results: Of 425 recruited depressed participants, 59 (13.9%) reported IPV at baseline, with physical IPV being the most frequently reported (69.5%). Reported IPV was associated with greater emotional distress, potentially higher food insecurity and higher rates of alcohol abuse. There were clear longitudinal trends in reported IPV with the majority of women no longer reporting IPV postpartum. However, some women reported IPV at later assessment points after not reporting IPV at baseline. Conclusions: There is a strong association between IPV and depression in pregnancy. IPV reports remit over time for the women in this study, although the reason for this reduction is not clear and requires further investigation.